Does an improved type of reporting lead to a better financial performance? - Ioana Sofian (Neacșu) (Contabilitate şi Informatică de Gestiune, 2019)
Research question: Is there a link between the type of report that a company publishes and its financial performance? Motivation: I draw on previous research that analyses the impact of integrated reporting on the firm’s valuation (Arguelles et al., 2015; Lee & Yeo, 2016; Barth et al., 2017; Zhou et al., 2017; Cosma et al., 2018) conducted mainly on South African samples (where integrated reporting is a mandatory practice) in order to develop an idea for future research based on early practices, a wider geographical distribution and an industry frequently eliminated from this type of studies. Idea: This paper aims to examine whether there is an association between publishing an improved type of report (e.g. integrated report) and financial performance indicators. Data: There were considered the 2013 and 2014 reports of 22 insurance companies listed to a stock exchange. Tools: There were applied different regressions with various variables (report type, integrated report, company size, leverage, return on assets, return on equity, Tobin’s Q and sustainability ranking) using the data sourced manually from the companies’ reports. Findings: Naming the 2013 report as “integrated” leads to changes in firm valuation (a positive and significant association between integrated report variable and Tobin’s Q), but does not cause improvements in terms of profitability (ROA or ROE). Contribution: This study contributes to the literature that examines the benefits of integrated reporting, without considering only mandatory cases and in the context of an influential industry, often eliminated from other studies.